How Coordination Trajectories Influence the Performance of Interorganizational Project Networks - Oliveira, Nuno; Lumineau, Fabrice (Organization Science, 2017)
This study examines how the joint use of integrators and contracts either enables or hampers coordination and, in turn, the performance of interorganizational project networks. Using extensive qualitative analyses and sociometric techniques, we investigated coordination among organizations during seven small- and medium-sized building projects. Our longitudinal study reveals how integrators develop connecting functions that, together with contracts’ steering functions, largely drive coordination dynamics. Further data analyses provide insight into how coordination hinges on the prevalence of connecting or steering, which may more or less fit with coordination needs in various project phases. Given these findings, we theorize the contingent nature of the interplay between the use of integrators and contracts throughout projects. Our findings are integrated into a process model of how coordination trajectories lead to different performance levels of interorganizational project networks. Our study has theoretical implications for the literature on project-based organizing and, more broadly, the literature on interorganizational coordination. The online appendix is available at https://doi.org/10.1287/orsc.2017.1151 .